Anatomic and Hemodynamic Plaque Characteristics for Subsequent Coronary Events - Lee, Seung Hun; Hong, David; Dai, Neng; Shin, Doosup; Choi, Ki Hong; Kim, Sung Mok; Kim, Hyun Kuk; Jeon, Ki-Hyun; Ha, Sang Jin; Lee, Kwan Yong; Park, Taek Kyu; Yang, Jeong Hoon; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives While coronary computed tomography angiography (CCTA) enables the evaluation of anatomic and hemodynamic plaque characteristics of coronary artery disease (CAD), the clinical roles of these characteristics are not clear. We sought to evaluate the prognostic implications of CCTA-derived anatomic and hemodynamic plaque characteristics in the prediction of subsequent coronary events. Methods The study cohort consisted of 158 patients who underwent CCTA with suspected CAD within 6–36 months before percutaneous coronary intervention (PCI) for acute myocardial infarction (MI) or unstable angina and age-/sex-matched 62 patients without PCI as the control group. Preexisting high-risk plaque characteristics (HRPCs: low attenuation plaque, positive remodeling, napkin-ring sign, spotty calcification, minimal luminal area <4 mm2, or plaque burden ≥70%) and hemodynamic parameters (per-vessel fractional flow reserve [FFRCT], per-lesion ΔFFRCT, and percent ischemic myocardial mass) were analyzed from prior CCTA. The primary outcome was a subsequent coronary event, which was defined as a composite of vessel-specific MI or revascularization for unstable angina. The prognostic impact of clinical risk factors, HRPCs, and hemodynamic parameters were compared between vessels with (160 vessels) and without subsequent coronary events (329 vessels). Results Vessels with a subsequent coronary event had higher number of HRPCs (2.6 ± 1.4 vs. 2.3 ± 1.4, P = 0.012), lower FFRCT (0.76 ± 0.13 vs. 0.82 ± 0.11, P < 0.001), higher ΔFFRCT (0.14 ± 0.12 vs. 0.09 ± 0.08, P < 0.001), and higher percent ischemic myocardial mass (29.0 ± 18.5 vs. 26.0 ± 18.4, P = 0.022) than those without a subsequent coronary event. Compared with clinical risk factors, HRPCs and hemodynamic parameters showed higher discriminant abilities for subsequent coronary events with ΔFFRCT being the most powerful predictor. HRPCs showed additive discriminant ability to clinical risk factors (c-index 0.620 vs. 0.558, P = 0.027), and hemodynamic parameters further increased discriminant ability (c-index 0.698 vs. 0.620, P = 0.001) and reclassification abilities (NRI 0.460, IDI 0.061, P < 0.001 for all) for subsequent coronary events. Among vessels with negative FFRCT (>0.80), adding HRPCs into clinical risk factors significantly increased discriminant and reclassification abilities for subsequent coronary events (c-index 0.687 vs. 0.576, P = 0.005; NRI 0.412, P = 0.002; IDI 0.064, P = 0.001) but not for vessels with positive FFRCT (≤0.80). Conclusion In predicting subsequent coronary events, both HRPCs and hemodynamic parameters by CCTA allow better prediction of subsequent coronary events than clinical risk factors. HRPCs provide more incremental predictability than clinical risk factors alone among vessels with negative FFRCT but not among vessels with positive FFRCT. Clinical Trial Registration PreDiction and Validation of Clinical CoursE of Coronary Artery DiSease With CT-Derived Non-INvasive HemodYnamic Phenotyping and Plaque Characterization (DESTINY Study), NCT04794868.